PERILAKU IBU HAMIL YANG BERKUNJUNG KE PUSKESMAS DALAM MANAJEMEN LAKTASI UNTUK KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PADANG BULAN KOTA MEDAN TAHUN 2012 - sari rahmadani; Eddy Syahrial; Lita Sri Andayani (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACK Lactation management is all that is needed to support successful breastfeeding so the baby can be fed properly. The goal of management is to increase the use of exclusive breastfeeding until the baby is 6 months old, with affection facilities. lactation Management begins during pregnancy (antenatal), immediately after birth (prenatal) and the postpartum period (post-natal). This research aims to determine the behavior of pregnant women in lactation management for the success of giving exclusive breastfeeding in the workplace of Health Center,Padang Bulan Medan. This research is a quantitative study that belongs to descriptive survey. The population in this study are pregnant women who visited the health center in Padang Bulan on August 2012, amounting to 39 people. The research sample is the entire population. Based on the results obtained that as many as 79.5% of pregnant women have moderate knowledge, also 79.5% have moderate attitude and 79.5% of them have moderate action aswell. In accordance with the results above, it is recommended that pregnant women  to further enhance the knowledge of lactation management. Health care workers should also be able to provide better service by providing lactation management information during antenatal care. The Department of Health is also expected to have to devise  a lactation management program in a structured, and train the health workers in the management of lactation and oversee its implementation in the field.